Impacts of the sustainable forestry initiative landscape level measures on hydrological processes - Azevedo, João (2009)
The effects on hydrological processes of the application of the landscape level measures included in the sustainable forestry initiative (SFI) program were analyzed through simulation. A landscape scenario where limitation of harvesting units’ size, imposition of a green-up interval, and establishment of streamside management zones (SMZ) were simulatedwas compared with a reference scenario where no SFI rules were followed. An intensively managed forested landscape located in East Texas, USA, was used as the study area. The HARVEST landscape model was used to simulate landscape pattern and a modified version of the APEX model was used to simulate hydrological processes. Water and sediment yields were generally small within the observation period and most of the runoff and erosion observed occurred during intense storm events. Water and sediment yield at the subarea level and water yield at the watershed level were similar in both scenarios. However, sediment yield at the watershed level was higher in the non-SFI scenario. The differences were due to the reduction in channel erosion resulting from the presence of SMZs. The effect of buffer zones in terms of sediment deposition was not different between scenarios, which can be attributed to the level slopes of the study area. Landscape measures of the SFI program, namely buffer zones, seem important in reducing channel degradation, particularly during major storm events, in intensively managed forest landscapes in East Texas.